New distributional record of oblique-banded grouper, Epinephelus radiatus (Day, 1868) from the St. Martin Island, Bangladesh - Hanıf, Md Abu; Sharker, Md. Rajib; Hossen, Shaharior; Bipu, Moniruzzaman (Aquatic Research, 2020)
Groupers are mostly found in the reef-associated marine habitat, of which some are pelagic and others are demersal. Recently, a grouper species called Oblique-banded grouper, Epinephelus radiatus (Day, 1868) was newly reported while conducting research work on the availability of reef-associated fishes in St. Martin Island. This species had never been reported to occur not only from this coral reef area but also from the water area of Bangladesh. E. radiatus was easily identified following morphological traits, especially color pattern. The findings of the present study added new distributional range for this grouper species from Bangladeshi water.